Rome, Italy. The collection of Roman statuary in the Villa Wolkonsky, the British (and former German) ambassador‘s seat in Rome, made available online on iDAI.objects/Arachne - Bockmann, Ralf; Bucolo, Raffaella (e-Forschungsberichte des DAI, 2020)
The Villa Wolkonsky is a former aristocratic residence in the centre of Rome built in the early 19th century, with a storied and important, but for a long time not easily accessible collection of antiquities. The collection has recently been systematically restored for better preservation and presentation on the premises of the residence, which today serves the British ambassador to Italy. After the restoration was completed, the Photo Library of the German Archaeological Institute at Rome was able to acquire the documentary photographic collection of the project and to conduct a new photographic mission. The academic part of the project has been carried out by Raffaella Bucolo. The collection is available online in the Arachne database.